DYNAMICS OF CARDIOVASCULAR SYSTEM PARAMETERS ON A BACKGROUND OF APPLICATION OF ADRENERGIC BLOCKERS IN CHILDREN WITH OBSTRUCTIVE HYPERTROPHIC CARDIOMYOPATHY - E.A. Tikhomirova; O.O. Kupriyanova; E.N. Basargina; A.P. Ivanov (Union of pediatricians of Russia, 2007)
The article is dedicated to the issue of curing children with obstructive form of hypertrophic cardiomyopathy. It presents a complex evaluation of adrenergic blockers influence on the clinical finding, heart rate disorder and vegetative regulation of heart rate, as well as prognosis for patients with obstructive form of the disease. Basing upon the findings, the article indicates criteria to evaluate the efficiency of curing children suffering from hypertrophic cardiomyopathy with adrenergic blockersKey words: hypertrophic cardiomyopathy, curing, children, adrenergic blockers.